“Hyphenation rules for words used in agriculture” (Eurasian Scientific Herald, 2023)
the very important and complex problems of the correct spelling of Geographical Names, the complexity of the issue of the correct spelling of toponyms is that they are in different languages, and in fact it is illuminated that they are written according to the rules of those languages.